USULAN PERAWATAN MESIN BENDING 90 DENGAN PENDEKATAN PREVENTIVE MAINTENANCE BERDASAR METODE KEANDALAN DAN FMEA DI PT. RINNAI INDONESIA-CIKUPA - Mohamad Syaripudin; Budiharjo Budiharjo; Diana Ayu Rostikawati (LPPM Universitas Bina Bangsa, 2022)
Based on sales data of PT. Rinnai Indonesia-Cikupa, there is an increase in sales of 15% stoves in 2021. Conditions that often occur are damage to production equipment including end forming, rolling, bending 90°, drilling, buffing, and stamping machines. This study aims to determine the level of performance of the bending machine 90° and proposed improvements with a preventive maintenance approach. The research was conducted during January-December 2021 using reliability analysis method and failure mode and effect analysis (FMEA) methods. Based on the reliability analysis. The overall availability (Ao) value of 88% is still below the world standard (≥90%). And from the failure mode and effect analysis, the RPN value is 352. This is due to the high downtime of the dominant component. Namely the encoder with a frequency of 86 times of damage and a downtime of 415 hours